The Relationship of Local Wisdom-Based Character Education on Young Females' Reproductive Health in Parigi Moutong - Indra Afrianto; Herlina Yusuf (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: This study evaluates the relationship between local wisdom-based character education and the reproductive health of young females in Parigi Moutong Regency. Character education strengthens adolescents' understanding and behavior regarding reproductive health, emphasizing values of integrity and responsibility. To assess how character education grounded in local wisdom influences reproductive health knowledge, attitudes, and behaviors among young females. Method: A quantitative cross-sectional design was employed, involving 150 respondents selected through purposive sampling. Data analysis utilized the Spearman correlation test. Result: The study found a significant positive relationship between character education based on local wisdom and reproductive health, with a correlation coefficient (r?) of 0.68 and a p-value of 0.001. This indicates that higher quality character education correlates with improved reproductive health knowledge, attitudes, and behaviors. Conclusion: Character education rooted in local wisdom significantly enhances reproductive health outcomes among adolescents. Integrating cultural values into education programs is vital for promoting healthier behaviors in rural communities.